2020
DOI: 10.22541/au.160569953.30220980/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of GmFAD3 expression alters responses to abiotic stress in soybean

Abstract: FAD3 play important roles in modulating membrane fluidity in response to various abiotic stresses. However, a comprehensive analysis of FAD3 in drought, salinity and heat stress tolerance is lacking in soybean. The present study assessed the functional role of fatty acid desaturase 3 to abiotic stress responses in soybean. We used Bean Pod Mottle Virus -based vector to alter expression of Glycine max omega-3 fatty acid desaturase . Higher levels of recombinant BPMV-GmFAD3 transcripts were detected in overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Moreover, we observed the expression of fatty acid desaturase 3 (FAD3) enzymes, which catalyze the conversion of linoleic acid to α-linolenic acid. Recent studies showed that fatty acid overexpression improved cold, drought and osmotic stress endurance in tobacco, soybean and tomato plants [94][95][96]. Subsequently, from these findings, we can come to the conclusion that AMP application may cause the activation of phospholipases, as well as phospholipid derived molecules, which are involved in plant defense systems [97].…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, we observed the expression of fatty acid desaturase 3 (FAD3) enzymes, which catalyze the conversion of linoleic acid to α-linolenic acid. Recent studies showed that fatty acid overexpression improved cold, drought and osmotic stress endurance in tobacco, soybean and tomato plants [94][95][96]. Subsequently, from these findings, we can come to the conclusion that AMP application may cause the activation of phospholipases, as well as phospholipid derived molecules, which are involved in plant defense systems [97].…”
Section: Discussionmentioning
confidence: 90%
“…Conversely, SAL-treated seedlings were less affected by this stress and exhibited a remarkably higher level of fatty acids. Singh et al ( 2020 ) indicated that fatty acids boosted drought and salinity stress tolerance in soybean plants. Therefore, these data suggest that SAL utilization may induce the activation of phospholipases and phospholipid-derived molecules, which are engaged in plant protection mechanisms (Hou et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%